Fenomena School of Crime dalam Kasus Tindak Pidana Berulang: Studi Kasus di Lembaga Pemasyarakatan Kelas IIA Jember - Panca Kursistin Handayani (Jurnal Online Psikogenesis, 2019)
Previous research on the effects of imprisonment or correctional practices on increasing recurrent crime is not clear enough. Mentioned in previous studies, although it was found data that people who have been imprisoned will tend to become recidivists (repeating their crimes) with a percentage of Â± 7-13%, but it cannot be ascertained how far the likelihood of recurring crimes is really caused by imprisonment. Based on these questions, this study aims to explore the phenomenon of the School of Crime in Class IIA Jember Lapas. The choice of location of the study is based on the incidence of recurrent crime which is quite high in the correctional institution. The results of this study are expected to provide an overview of other factors beyond guidance that are often not detected by the Lapas, so that efforts to anticipate and change the atmosphere in guidance can be done to overcome this phenomenon.The qualitative method with the Phenomenology Case Study approach was used for this purpose, with the FGD and in-depth interviews as the main data collection methods. The research subjects used were 9 recidivist prisoners (6 for FGDs and 3 for in-depth interviews). Analysis of the data used is Interpretative Phenomelogical Analysis (IPA) which is used to make conclusions about the themes of the research findings.The results of the study found that: First, prisons provide an opportunity to learn about characters that are considered better, as well as strategies and methods used in committing crimes from fellow prisoners. Secondly, prisons also provide an opportunity to add social networks to friendship and connections, which later has the potential as a supporting factor or risk factor for the formation of repetition of crime after the prison is released. Third, criminal tendencies and family problems become risk factors or protective factors for the formation of recurrent crime